Use of Systemic Steroids, Hormone Replacement Therapy, or Oral Contraceptives Is Associated with Decreased Implant Survival in Women - Michelle Y. Zou; Robert E. Cohen; Brendon L. Ursomanno; Lisa M. Yerke (Dentistry Journal, 2023)
Background: Systemic steroids, such as prednisone, hormonal replacement therapies, or oral contraceptives, are commonly prescribed to women who might also be receiving dental implant therapy. However, the effect of these medications on dental implant survival is unknown. Methods: The medical and dental records of individuals with dental implants (N = 1480 implants) who visited a postgraduate periodontics clinic between 2000 and 2017 were initially considered. Those younger than 21 years old, pregnant, or male were excluded according to the study’s exclusion criteria. The presence of systemic diseases and conditions was assessed. Implant failure rates among female patients using systemic steroids, hormone replacement therapy, or oral contraceptives were compared with failure rates among patients not taking those medications. Results: The implant failure rate for the 65 implants in patients taking steroid medications was 7.69%; the failure rate for the 712 implants in patients not taking steroids was 1.54% (p < 0.001). After adjusting for smoking and the presence of diabetes, that relationship persisted, with an 8.47% implant failure rate for the 59 implants in patients taking steroids (vs. 1.54% failure for the 585 implants in patients not taking steroids; p < 0.001). Regression analyses demonstrated that the odds of implant failure versus success were 5.31 times greater in patients taking systemic steroids, hormone replacement therapy, or oral contraceptives (p < 0.05). No statistically significant differences in patient plaque control were found between the experimental and control groups. Conclusions: Among women, the use of systemic steroids is associated with a five-fold increase in the rate of dental implant failure, regardless of the presence of smoking or diabetes.